2019
DOI: 10.3892/mmr.2019.10827
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoma Paridis total saponins alleviate H2O2‑induced oxidative stress injury by upregulating the Nrf2 pathway

Abstract: Rhizoma Paridis total saponins (RPTS) is an active substance isolated from the traditional Chinese medicine Rhizoma Paridis, which possesses multiple biological activities. The aim of the present study was to explore the roles and mechanisms of RPTS in oxidative stress injury of ARPE-19 human retinal pigment epithelial cells. Cell viability, reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP) and apoptosis were determined by Cell Counting kit-8 assay and flow cytometry, respectively. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In our study, the results showed that Nrf2 was blocked into the nucleus in the LPS-ENR group ( Figure 4 ), while the transfer of Nrf2, the mRNA expression level of Nrf2, and the protein expression level of Nrf2 were improved by MRGD and MRGDE ( Figure 3 A and B). Once in the nucleus, Nrf2 bonded to the ARE, thereby activating the mRNA expressions of several downstream genes such as HO-1 and NQO1 in the nucleus ( Zhang et al, 2019 ; Zhao et al, 2020 ). A report showed that trehalose adjusts the REDOX in cells via activating the Nrf2 pathway and increasing the mRNA expression levels of genes GPX1, CAT, SOD1, NQO1, and HO-1 ( Xie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results showed that Nrf2 was blocked into the nucleus in the LPS-ENR group ( Figure 4 ), while the transfer of Nrf2, the mRNA expression level of Nrf2, and the protein expression level of Nrf2 were improved by MRGD and MRGDE ( Figure 3 A and B). Once in the nucleus, Nrf2 bonded to the ARE, thereby activating the mRNA expressions of several downstream genes such as HO-1 and NQO1 in the nucleus ( Zhang et al, 2019 ; Zhao et al, 2020 ). A report showed that trehalose adjusts the REDOX in cells via activating the Nrf2 pathway and increasing the mRNA expression levels of genes GPX1, CAT, SOD1, NQO1, and HO-1 ( Xie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our evidence fully introduces PUN among antioxidant natural substances able to protect RPE from oxidative stress. In this regard, there is a wide research line that describes compounds of natural origin capable of protecting RPE, via Nrf2 activation, against various oxidative stimuli (mainly H 2 O 2 ) [ 29 , 30 , 31 ]. However, the fact that, in our experimental paradigm, PUN protects epithelium against UV radiation (the main natural exogenous stressor for RPE) makes it particularly noteworthy, compared to other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have proved that Nrf2 is an emerging regulator of cellular resistance to oxidative stress. Some natural products (such as apigenin, quercetin, gypenosides, genipin, rhizoma paridis, escin, and astaxanthin) have also been shown to have protective effects against the oxidative stressed ARPE-19 cells associated with Nrf2 signaling [28,[57][58][59][60][61][62][63]. In our study, we found that treatment with 1 mM H 2 O 2 for 24 h significantly induced a serious oxidative cell damage and apoptosis in ARPE-19 cells (Figures 1 and 2).…”
mentioning
confidence: 51%